Biocompatibility of gentamicin-coated hydroxyapatite (Ha) with osteoblast - Mohd Azam Khan Goriman Khan; Fauziah O. (2010)
This study was carried out to compare the surface morphological changes and cell-to-cell attachment with different concentrations of gentamicin-coated hydroxyapatite (HA) on the osteoblast cell lines. Osteoblast cell lines were cultured and maintained in complete medium, 1:1 HAM’s F12 Medium Dulbecco's modified Eagle's medium without phenol red (DMEM) and incubated at 37oC in 5% CO2. The cell lines were treated with gentamicin-coated HA and undergone the 3-(4,5-di-methylthiazol-2-yl)-2,5- diphenyl tetrazolium bromide (MTT) assay. After 72 hours treatment, the gentamicin-coated HA was processed for viewing the morphological changes by using scanning electron microscopy. The MTT assay results indicated that varying concentrations of gentamicin coated hydroxyapatite do not significantly affect viability of osteoblast. The osteoblast-like cells attached and spread well on the surface of hydroxyapatite and grew into the pores. In conclusion, the gentamicin-coated HA is biocompatible towards osteoblast.